Análise do plano de permanência de estudantes da Universidade Federal do Pampa - Rios, Rafaela (2016)
Considering the advent and the expansion of the National Programme of Student Assistance (PNAES), and its requirement as the establishment of mechanisms for monitoring and evaluation by the federal universities, this research is thematic actions subsidized by student assistance policy. This study aimed to analyze the actions performed in Permanence Plan UNIPAMPA in terms of promoting results regarding permanence, avoidance, retention and completion of the institution's students. Therefore, there was a case study with a qualitative and quantitative approach, as well as exploratory and descriptive, with the following sources of evidence: literature, documentary research, participant observation and questionnaire. The instrument was structured based on each research subject: beneficiaries of UNIPAMPA the Stay Plan in the period 2009-2015 (regular and former students); Deans of student assistance (or equivalent) of IFES; Deans of Graduate and Student of UNIPAMPA assistance; and representatives of NUDEs, which are the sectors responsible for the materialization of student assistance actions in the study IFE. For the beneficiary students Permanence Plan, 543 shares were obtained, exceeding the calculated minimum sample size (367 students) for the defined population (4,478 students), and around 4,605 emails were fired. The questionnaires for student assistance managers were sent to 63 Brazilian IFES, yielding 14 returns, including UNIPAMPA. There was no return of the Dean of Undergraduate study IFE. Considering professionals of nudes, 8 answers were obtained. Data analysis was performed using descriptive statistics and the content analysis method, starting for the conclusions. As a result, it was found that no information was found on the websites or these were insufficient on the way the IFES evaluate their permanence actions, with a view to compliance with Decree 7234/2010-PNAES, with respect to its Article 5, which states that "it is for the federal higher education institutions establish mechanisms for monitoring and evaluation of PNAES". The results indicate that the actions taken in Permanence Plan contribute to promoting results as residence and academic success of students, but they are not the only factors to be considered by management. It was concluded that the IFES are advancing in the implementation of mechanisms to monitor and evaluate the implementation of PNAES.